2023
DOI: 10.11114/smc.v11i5.6033
|View full text |Cite
|
Sign up to set email alerts
|

A Systemic Functional Linguistic Analysis of Clauses Relationship in Luke Gospel Text, Janji Baru Using Kupang Malay

Abstract: This paper reports on a functional linguistics study of clauses relationship in which it is included as textual meta function of meaning. This textual metafunction is on the level of lexicogrammar. Semantic sequence of figures is realized by a clause complexes series. This paper focused on relationship types between clauses, interdependency and logico-semantic relationship. Data were taken from A Bible, New Testament using Kupang Malay called Janji Baru, especially in Luke of Gospel text. The analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The study suggested that the use of noun phrases had a positive impact on the grasping ability of readers. Ngongo et al (2023) conducted a study in which the focus was on the logicosemantic linkages in Kupang Malay version of the Luke Gospel. The study intended to explore the interdependence of taxis and the relations among projection, expansion and semantics.…”
Section: Syntactic Complexitymentioning
confidence: 99%
“…The study suggested that the use of noun phrases had a positive impact on the grasping ability of readers. Ngongo et al (2023) conducted a study in which the focus was on the logicosemantic linkages in Kupang Malay version of the Luke Gospel. The study intended to explore the interdependence of taxis and the relations among projection, expansion and semantics.…”
Section: Syntactic Complexitymentioning
confidence: 99%